2016
DOI: 10.1097/md.0000000000004494
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of pretreated serum lactate dehydrogenase level in nasopharyngeal carcinoma among Chinese population

Abstract: Background:A large number of studies have investigated the prognostic value of pretreated lactate dehydrogenase (LDH) level in nasopharyngeal carcinoma (NPC) patients while the role of it was inconsistent and inconclusive. Hence, the aim of the current study was to conduct a meta-analysis of all published studies to quantify the prognostic impact of pretreated serum LDH in NPC for Chinese population.Objectives:The aim of the current study was to conduct a meta-analysis of all published studies to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…In addition, this study was examined in a single center. So, the following research should be done on a large-scale and using multicenter prospective validation of NPC groups; Third, we were just concerned with the impact of systemic inflammation–based prognostic factors on the prognosis of patients with NPC, and we did not compare the novel inflammation-based prognostic system with other traditional prognostic factors, such as Epstein-Barr Virus DNA or lactate dehydrogenase (LDH) [41,42,43]. Thus, whether the I stage is more useful in predicting OS in patients with NPC as compared to other traditional prognostic factors remains to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study was examined in a single center. So, the following research should be done on a large-scale and using multicenter prospective validation of NPC groups; Third, we were just concerned with the impact of systemic inflammation–based prognostic factors on the prognosis of patients with NPC, and we did not compare the novel inflammation-based prognostic system with other traditional prognostic factors, such as Epstein-Barr Virus DNA or lactate dehydrogenase (LDH) [41,42,43]. Thus, whether the I stage is more useful in predicting OS in patients with NPC as compared to other traditional prognostic factors remains to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond traditional prediction strategies, some recent studies reported that various clinical risk factors, such as hemoglobin, lactate dehydrogenase level, neutrophil-to-lymphocyte ratio, and platelet counts, were associated with poor survival (10)(11)(12)(13). However, the clinical utility of these factors was limited and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 After evaluating 14 803 patients with an NC diagnosis, Zhang et al reported that high LDH levels before treatment were associated with poor overall, progression-free and distant metastasis-free survival. 42 In this study, significant variables were determined as age, weight loss, initial NLR, initial LDH, initial hemoglobin, radiotherapy duration, tumor diameter, number of cases undergoing concurrent chemotherapy, and T and N stages. Machine learning is a subfield of artificial intelligence that involves development of algorithms that obtain model and parameters best representing the available data.…”
Section: Discussionmentioning
confidence: 99%